Effects of multitasking on retention and topic interest. (February 2016) - Dindar, Muhterem; Akbulut, Yavuz
Abstract: A recent and pervasive "urban legend" in education describes contemporary students as digital natives and effective multitaskers. The current study investigated the effects of sequential and concurrent multitasking scenarios on content retention and topic interest in a multimedia learning environment. Five hundred and seventy two undergraduate students were randomly assigned to one of the seven conditions in which either sequential or concurrent multitasking scenarios were simulated through a web-based system. While the sequential conditions either required switching between instructional and distractive videos or between two instructional videos, the concurrent multitasking scenarios involved online chatting while watching the videos. The relationships between digital device experience, daily media exposure, current multitasking habits, working memory components, and content retention were also investigated. Findings revealed that sequential multitasking did not interfere with retention whereas concurrent multitasking interfered with both retention and topic interest. Digital device experience and daily multitasking habits were not related with retention. Furthermore, daily media exposure was negatively associated with the retention, particularly in the longer sequential multitasking scenarios. Finally, different types of multitasking were related with different working memory constructs. Highlights: Multitasking skills of digital natives are empirically questioned. Concurrent multitasking rather than the sequential one interfered with learning. Affective implications of multitasking varied among different topics. Popular digital nativity traits did not contribute to multitasking success. Working memory constructs were related to different multitasking conditions.